Examining the Non-linear Impact of Government External Debt And Sukuk on Indonesia’s Economic Growth - Fahmaninda Listiyani; Zulfatul Ruscitasari (Universitas Alma Ata, 2026)
Purpose: This study examines the non-linear impact of Indonesia’s external debt on economic growth using the debt threshold curve proposed by Pattillo. It also compares external debt with sukuk, highlighting that Islamic bonds are relatively more stable and that sukuk, as a rapidly developing Islamic finance instrument, may follow a U-shaped relationship with growth. In this framework, sovereign sukuk (SBSN) are expected to support Indonesia’s economic growth in the long term. Method: The study employs the ARDL (Autoregressive Distributed Lag) approach to estimate the effect of external debt and SBSN on GDP, and uses the quadratic axis-of-symmetry formula to derive the optimal ratios of external debt and sukuk to GDP. Results: The findings reveal an inverted U-shaped relationship between external debt and growth, consistent with the debt threshold hypothesis, and a U-shaped relationship for sukuk, indicated by a negative first-order sukuk coefficient and a positive squared term. Conclusion: These results imply that while excessive external debt ultimately depresses growth, scaling up SBSN can foster long-run economic expansion. Implication: Though current evidence is constrained by short sukuk time series and lack of sectoral SBSN data, future research should use richer, multi-country data, additional controls, and sector-disaggregated SBSN information. Originality: The study is one of the first to jointly model external debt and sukuk using non-linear specifications, filling a gap in empirical work linking SBSN and GDP and offering a basis for subsequent research on sukuk’s role in Indonesia’s economic development.